Robin Helby (1938–2024) – a giant of Australasian palynology - James B. Riding; Clinton B. Foster; Carey Hannaford; Mike Macphail; Daniel J. Mantle; Geoffrey Playford; Jill Stevens; Geoff Wood (Palynology, 2026)

Impact of Dietitian-Delivered Motivational Interviewing Within a Food is Medicine Intervention Targeting Adults Living With and Beyond Cancer - Ashlea C. Braun; James Portner; Elizabeth M. Grainger; Steven K. Clinton; Menglin Xu; Amy Darragh; Keeley J Pratt; Lindy L. Weaver; Colleen K. Spees (Journal of Cancer Education, 2025)

Coffee, Phosphoinositide 3-Kinase Signaling Pathway, and Prostate Cancer: A Prospective Study in the Health Professionals Follow-Up Study - Rui Song; Konrad H. Stopsack; Junkun Ren; Lorelei A. Mucci; Steven K. Clinton; Massimo Loda; Molin Wang; Edward L. Giovannucci; Kathryn M. Wilson; Stephanie A. Smith-Warner (Journal of the Academy of Nutrition and Dietetics, 2025)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Aspirin use and prostate tumor angiogenesis - Benjamin C. Fu; Kai Wang; Lorelei A. Mucci; Steven K. Clinton; Edward L. Giovannucci (Cancer Causes & Control, 2022)

Vascular morphology differentiates prostate cancer mortality risk among men with higher Gleason grade - Meng Yang; Ke Zu; Lorelei A. Mucci; Jennifer R. Rider; Michelangelo Fiorentino; Steven K. Clinton; Massimo Loda; Meir J. Stampfer; Edward Giovannucci (Cancer Causes & Control, 2016)

The herpes simplex virus type 1 (HSV-1) latency-associated transcript (LAT) protects cells against cold-shock-induced apoptosis by maintaining phosphorylation of protein kinase B (AKT) - Dale Carpenter; Chinhui Hsiang; Xianzhi Jiang; Nelson Osorio; Lbachir BenMohamed; Clinton Jones; Steven L. Wechsler (Journal of NeuroVirology, 2015)

“AmaRosa,” a Red Skinned, Red Fleshed Fingerling with High Phytonutrient Value - Charles R. Brown; Isabel Vales; Solomon Yilma; Steven James; Brian Charlton; Darrin Culp; Dan Hane; Clinton Shock; Eric Feibert; Mark Pavek; Richard Knowles; Richard Novy; et al. (American Journal of Potato Research, 2012)

Phenotypic variation and host interactions of Xenorhabdus bovienii SS‐2004, the entomopathogenic symbiont of Steinernema jollieti nematodes - Darby R. Sugar; Kristen E. Murfin; John M. Chaston; Aaron W. Andersen; Gregory R. Richards; Limaris deLéon; James A. Baum; William P. Clinton; Steven Forst; Barry S. Goldman; Karina C. Krasomil‐Osterfeld; Steven Slater; et al. (Environmental Microbiology, 2012)
Summary Xenorhabdus bovienii (SS‐2004) bacteria reside in the intestine of the infective‐juvenile (IJ) stage of the entomopathogenic nematode, Steinernema jollieti. The recent sequencing of the X. bovienii genome facilitates its use as a model to understand host – symbiont interactions. To provide a biological foundation for such studies, we characterized X. bovienii in vitro and host interaction phenotypes. Within the nematode host X. bovienii was contained within a membrane bound envelope that also enclosed the nematode‐derived intravesicular structure. Steinernema jollieti nematodes cultivated on mixed lawns of X. bovienii expressing green or DsRed fluorescent proteins were predominantly colonized by one or the other strain, suggesting the colonizing population is founded by a few cells. Xenorhabdus bovienii exhibits phenotypic variation between orange‐pigmented primary form and cream‐pigmented secondary form. Each form can colonize IJ nematodes when cultured in vitro on agar. However, IJs did not develop or emerge from Galleria mellonella insects infected with secondary form. Unlike primary‐form infected insects that were soft and flexible, secondary‐form infected insects retained a rigid exoskeleton structure. Xenorhabdus bovienii primary and secondary form isolates are virulent towards Manduca sexta and several other insects. However, primary form stocks present attenuated virulence, suggesting that X. bovienii , like Xenorhabdus nematophila may undergo virulence modulation.

Alpine Russet: A Potato Cultivar Having Long Tuber Dormancy Making it Suitable for Processing from Long-term Storage - Jonathan L. Whitworth; Richard G. Novy; Jeffrey C. Stark; Joseph J. Pavek; Dennis L. Corsini; Steven L. Love; Nora Olsen; Sanjay K. Gupta; Tina Brandt; M. Isabel Vales; Alvin R. Mosley; Solomon Yilma; et al. (American Journal of Potato Research, 2011)

Tomato-based food products for prostate cancer prevention: what have we learned? - Hsueh-Li Tan; Jennifer M. Thomas-Ahner; Elizabeth M. Grainger; Lei Wan; David M. Francis; Steven J. Schwartz; John W. Erdman; Steven K. Clinton (Cancer and Metastasis Reviews, 2010)

Identification of herpes simplex virus type 1 proteins encoded within the first 1.5 kb of the latency-associated transcript - Gail Henderson; Tareq Jaber; Dale Carpenter; Steven L. Wechsler; Clinton Jones (Journal of NeuroVirology, 2009)

Cellular FLIP can substitute for the herpes simplex virus type 1 latency-associated transcript gene to support a wild-type virus reactivation phenotype in mice - Ling Jin; Dale Carpenter; Megan Moerdyk-Schauwecker; Adam L Vanarsdall; Nelson Osorio; Chinhui Hsiang; Clinton Jones; Steven L Wechsler (Journal of NeuroVirology, 2008)

A speculated ribozyme site in the herpes simplex virus type 1 latency-associated transcript gene is not essential for a wild-type reactivation phenotype - Dale Carpenter; Sukhpreet Singh; Nelson Osorio; Chinhui Hsiang; Xianzhi Jiang; Ling Jin; Clinton Jones; Steven L. Wechsler (Journal of NeuroVirology, 2008)

Identification of two small RNAs within the first 1.5-kb of the herpes simplex virus type 1–encoded latency-associated transcript - Weiping Peng; Olga Vitvitskaia; Dale Carpenter; Steven L Wechsler; Clinton Jones (Journal of NeuroVirology, 2008)

Reactivation phenotype in rabbits of a herpes simplex virus type 1 mutant containing an unrelated antiapoptosis gene in place of latency-associated transcript - Ling Jin; Guey-Chuen Perng; Dale Carpenter; Kevin R Mott; Nelson Osorio; Julia Naito; David J Brick; Clinton Jones; Steven L Wechsler (Journal of NeuroVirology, 2007)

A mutant deleted for most of the herpes simplex virus type 1 (HSV-1) UOL gene does not affect the spontaneous reactivation phenotype in rabbits - David Chan; Jacob Cohen; Julie Naito; Kevin R Mott; Nelson Osorio; Ling Jin; Nigel W Fraser; Clinton Jones; Steven L Wechsler; Guey Chuen Perng (Journal of NeuroVirology, 2006)

The latency-related gene encoded by bovine herpesvirus 1 can suppress caspase 3 and caspase 9 cleavage during productive infection - Gail Henderson; Guey-Chuen Perng; Anthony B Nesburn; Steven L Wechsler; Clinton Jones (Journal of NeuroVirology, 2004)

Opposite association of two PPARG variants with cancer: overrepresentation of H449H in endometrial carcinoma cases and underrepresentation of P12A in renal cell carcinoma cases - Wendy Smith; Xiao-Ping Zhou; Keisuke Kurose; Xin Gao; Farida Latif; Todd Kroll; Kokichi Sugano; Stephen Cannistra; Steven Clinton; Eamonn Maher; Thomas Prior; Charis Eng (Human Genetics, 2001)